PHYTOCHEMICAL, PHARMACOLOGICAL AND BIOLOGICAL PROFILES OF TRAGIA SPECIES (FAMILY: EUPHORBIACEAE) - Reddy, Bonam Srinivasa; Rao, Nadendla Rama; Vijeepallam, Kamini; Pandy, Vijayapandi (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Tragia belongs to the family Euphorbiaceae which contains about 152 species. Interestingly, most of the earlier investigations have been done using only five Tragia species, namely, Tragia involucrata, Tragia cannabina, Tragia spathulata, Tragia plukenetii, and Tragia benthamii. The objective of the present review is to compile the phytochemical, pharmacological and biological studies of the selected five Tragia species reported in the literature. Methods: The reported data/information was retrieved mainly from the online databases of PubMed (MEDLINE), EMBASE and Botanical Survey of India. Results: The present review elaborated the phytochemical, pharmacological and biological properties of the selected five Tragia species obtained from recent literature. Conclusion: This review provides a basis for future investigation of Tragia species and, especially for those species that have not been explored for biological and pharmacological activities.